The silence : a novel - DeLillo, Don (Scribner, 2020)
It is Super Bowl Sunday in the year 2022. Five people, dinner, an apartment on the east side of Manhattan. The retired physics professor and her husband and her former student waiting for the couple who will join them from what becomes a dramatic flight from Paris. The conversation ranges from a survey telescope in North-central Chile to a favorite brand of bourbon to Einstein's 1912 Manuscript on the Special Theory of Relativity. Then something happens and the digital connections that have transformed our lives are severed.